Cytological Analysis Of Female Patients With Sigmoidal Colpopoiesis Depending On The Duration Of Operation - Yakubov Munis Zokirovich (Academia One, 2024)
The aim of the study is to study the cytological characteristics of the sigmoid colon after vaginoplasty in women of different periods.
Keywords: using; cytological; sigmoid